2020
DOI: 10.21203/rs.2.22869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomic composition and diversity of the gut microbiota in relation to habitual diet in Korean adults

Abstract: Background: Little is known of the relationship between the Korean habitual diet and gut microbiota composition. We investigated associations of habitual dietary intake of foods and nutrients with the taxonomic composition and diversity of gut microbiota in 222 Korean adults aged 18-58 years in a cross-sectional study. Gut microbial taxonomic composition and diversity data were obtained by 16S rRNA gene sequencing of bacterial DNA extracted from fecal samples. Habitual diet for the previous year was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Five studies were done in vitro/vivo, except for two studies (Sugimoto et. al.,[85]; Noh et al, [83]) which were done in the Asian population i.e., Korea and Japan. The age range for the human population was between 18 to 60 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were done in vitro/vivo, except for two studies (Sugimoto et. al.,[85]; Noh et al, [83]) which were done in the Asian population i.e., Korea and Japan. The age range for the human population was between 18 to 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lomartire et al, [86] showed that the biologically active content of green seaweed has anticancer, antimutagenic, antioxidant, antibacterial, and anticoagulant activities [89], and this antioxidant activity was due to the presence of pheophorbide, a chlorophyll-related compound, implying that seaweed can serve as a functional food. Noh et al, [83] showed that seaweed vegetables are good sources of fiber, which is a good substrate as an energy source for the gut microbiota [90]. Shannon et al, [54] showed that fiber and polyphenol-rich seaweeds can remarkably increase the number of commensal bacteria in vitro and their making of short-chain fatty acids after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation